Rekviem za samostansko knjižnico --- ali aleluja? - Špelič, Miran (Knjižnica, 2011)
Purpose: The contribution briefly summarizes the importance of books for monasticism, especially the sacred books, which monks learned very often almost entirely by heart. Books had an important role for the support of individual spiritual growth and as such were often also a part of the orders' Rules. In monasteries books enabled work to monks (labora); they were intended for the church and worship (ora); but most of all they were intended for study in the solitude of the cell or in the library. And the monasteries of medieval and early modern Europe could not miss the richly stocked libraries. In the Franciscan friary in Ljubljana books were also used for studies. Their library was one of the largest at the time of Sigismund Škerpin (18th century) in Ljubljana. Methodology/approach: the contribution summarizes particular theoretical frameworks, linking them to practical knowledge and experience. The monastic Rules are also included. Results: tuday the stock of the Ljubljana Franciscan monastery library is still rising, but the question of its future remains open as the number of its readers and visitors declines. Of course, as manuscript heritage was not destroyed by the print revolution, so the digitization will not end the traditional forms of books and libraries, but in the future it will be necessary to change the overall perspective if we want to keep the library alive. There are some possibilities transforming the nowadays monastic libraries into new forms with the change of the purpose of the libraries into museums or research laboratories. Research limitations: since this is only a short outline of the issues monastic libraries have, the present contribution can be seen as an introduction to a possible more indepth study, which would enlighten their current state. Synchronic and diachronic studies of individual libraries of various orders in Slovenia are required with analytical comparison of obtained results in order to get reliable conclusions. Originality/practical implications: the author draws attention to an important cultural issue, which is partly ignored by librarians and other scientific communities.
Keywords: samostanske knjižnice; knjižno gradivo; svete knjige; frančiškani; digitalizacija; digitization; Slovenia; Slovenija; zgodovinski pregledi